Vascular Abnormalities and the Role of Vascular Endothelial Growth Factor in the Epileptic Brain - Ogaki, Ari; Ikegaya, Yuji; Koyama, Ryuta (Frontiers in Pharmacology, 2020)
Epilepsy is a chronic neurological disorder generally defined to be caused by excessive neuronal activity. Thus, excessive neuronal activity is the main target of the currently used anti-epileptic drugs (AEDs). However, as many as thirty percent of epileptic patients show drug resistance to currently available AEDs, which suggests that epilepsy should be attributed not only to neuronal cells but also to other brain cells, such as glial cells and vascular cells. Astrocytes, pericytes, and endothelial cells in particular comprise the blood-brain-barrier (BBB), which tightly regulates the exchange of substances between the brain parenchyma and the circulating blood. It has been proposed that BBB dysfunction, especially barrier leakage, exacerbates epileptic progression, and conversely, that epileptic seizures induce barrier leakage. Furthermore, several studies have shown that BBB dysfunction is one of the main causes of drug resistance in epilepsy. To better understand the mechanisms that link BBB dysfunction and intractable epilepsy to gain insights for the future development of treatments, we review and discuss the relationships between epilepsy and brain vascular abnormalities, mainly by focusing on vascular malformation, BBB dysfunction, and excessive angiogenesis. Because these abnormalities have been reported to be caused by vascular endothelial growth factor (VEGF) in the ischemic brain, we discuss the possible role of VEGF in vascular abnormalities in the epileptic brain, in which the upregulation of VEGF levels has been reported. Both glial cells and endothelial cells express VEGF receptors (VEGFRs); thus, these cells are likely affected by increases in VEGF during seizures, which in turn could cause vascular abnormalities. In this review, we review the possible role of VEGF in epilepsy and discuss the mechanisms that link vascular abnormalities and intractable epilepsy.